HOW READING MATURITY INFLUENCES READING COMPREHENSION ACHIEVEMENT - Robby Rahmad; Ridha Ilma; Deta Desvitasari (Jurnal Genta Mulia, 2024)
One of the most crucial abilities that kids need to develop is reading. Because reading maturity is the achievement of reading abilities and information, having high reading maturity can benefit kids in reading. Thus, utilizing cluster random sampling procedures, this researchers examined the relationship and impact of reading maturity and reading comprehension achievement on a sample of 105 students enrolled in the tenth grade. The reading maturity questionnaire and the reading comprehension accomplishment test were employed in this study, and regression analysis and the analysis employed the Pearson Product Moment correlation coefficient. As a result, the r-value was greater (0.243 > 0.168) than the r-table for df=94. Similar to this, the significance level (p) (sig.2-tailed) was 0.017, less than 0.05 (0.017 < 0.05). It was determined that there was a considerable positive association and influence between reading comprehension achievement and reading maturity.